Applying DWT and PCA with Artificial Neural Network for FACE RECOGNITION (مجلة الواحات للبحوث والدراسات, 2021)
This manuscript presents, Face recognition by combining different extraction approaches combining PCA (principal Component Analysis), DWT (Discrete wavelet transform) and neural networks. This method consists of  four steps: i) Preprocessing, ii) Dimension reduction using DWT, iii)  feature extraction using PCA and  iv) classification using neural  network. To validate this work, we have tested this technique on frontal images of the ORL and Yale databases.Keywords - Face Recognition, Biometrics, PCA, Neural Networks, Feature extraction, eigenfaces , DWT.